An Occupational Safety And Health Management System To Minimize Work Accidents - Indriyani Indriyani; Djoko Dwi Kusumojanto (Department of Management FEB Unhas, 2020)
Industrial activities are planning and controlling well through the implementation of occupational safety and Health management The purpose of this research is to know the implementation of occupational health and safety management in order to minimize work accidents. This research is done by qualitative research methods with a type of descriptive research. The results showed the planning and implementation of occupational safety and health management that has been well implemented so as to minimize work accidents.